Genetic and epigenetic factors which modulate differentiation propensity in human pluripotent stem cells. (25th January 2018) - Keller, Alexander; Dziedzicka, Dominika; Zambelli, Filippo; Markouli, Christina; Sermon, Karen; Spits, Claudia; Geens, Mieke
Abstract: BACKGROUND: Human pluripotent stem cell (hPSC) lines are known to have a bias in their differentiation. This gives individual cell lines a propensity to preferentially differentiate towards one germ layer or cell type over others. Chromosomal aberrations, mitochondrial mutations, genetic diversity and epigenetic variance are the main drivers of this phenomenon, and can lead to a wide range of phenotypes. OBJECTIVE AND RATIONALE: Our aim is to provide a comprehensive overview of the different factors which influence differentiation propensity. Specifically, we sought to highlight known genetic variances and their mechanisms, in addition to more general observations from larger abnormalities. Furthermore, we wanted to provide an up-to-date list of a growing number of predictive indicators which are able to identify differentiation propensity before the initiation of differentiation. As differentiation propensity can lead to difficulties in both research as well as clinical translation, our thorough overview could be a useful tool. SEARCH METHODS: Combinations of the following key words were applied as search criteria in the PubMed database: embryonic stem cells, induced pluripotent stem cells, differentiation propensity (also: potential, efficiency, capacity, bias, variability), epigenetics, chromosomal abnormalities, genetic aberrations, X chromosome inactivation, mitochondrial function, mitochondrial metabolism, genetic diversity, reprogramming, predictive marker, residual stem cell, clinic. Only studies in English were included, ranging from 2000 to 2017, with a majority ranging from 2010 to 1017. Further manuscripts were added from cross-references. OUTCOMES: Differentiation propensity is affected by a wide variety of (epi)genetic factors. These factors clearly lead to a loss of differentiation capacity, preference towards certain cell types and oftentimes, phenotypes which begin to resemble cancer. Broad changes in (epi)genetics, such as aneuploidies or wide-ranging modifications to the epigenetic landscape tend to lead to extensive, less definite changes in differentiation capacity, whereas more specific abnormalities often have precise ramifications in which certain cell types become more preferential. Furthermore, there appears to be a greater, though often less considered, contribution to differentiation propensity by factors such as mitochondria and inherent genetic diversity. Varied differentiation capacity can also lead to potential consequences in the clinical translation of hPSC, including the occurrence of residual undifferentiated stem cells, and the transplantation of potentially transformed cells. WIDER IMPLICATIONS: As hPSC continue to advance towards the clinic, our understanding of them progresses as well. As a result, the challenges faced become more numerous, but also more clear. If the transition to the clinic is to be achieved with a minimum number of potential setbacks, thorough evaluation of the cells will be an absolute necessity. Altered differentiation propensity represents at least one such hurdle, for which researchers and eventually clinicians will need to find solutions. Already, steps are being taken to tackle the issue, though further research will be required to evaluate any long-term risks it poses.